Density and distribution pattern of Polinices sp. in Kuala Cangkoi and Ujong Pancu beach, Indonesia - Octavina Chitra; Zahara Nadia; Feranita Fachri Rania; Muntazir Muntazir (BIO Web of Conferences)
Polinices sp. is a genus of the Naticidae family that lives in the intertidal zone with tidal influence and soft textured substrates. This research was conducted in March 2022, located in the waters of Kuala Cangkoi, Banda Aceh and Ujong Pancu, Aceh Besar. The purpose of this study was to determine the density and distribution pattern of Polinices with Kuala Cangkoi and Ujong Pancu water quality. The method used in this study was purposive sampling method. The identification results found in both research locations are Polinices mammilla (Linnaeus, 1758). The average density value of Polinices obtained in Kuala Cangkoi was 1.6 ind/m2 and in Ujong Pancu 1.9 ind/m2. The distribution pattern found in both research locations is random. Water parameters include temperature ranging from 30°C - 32°C in both locations. The salinity obtained in both research locations was 20‰. The acidity (pH) obtained was 8.4 in Kuala Cangkoi and 7.6 in Ujong Pancu. The type of substrate obtained is sandy loam and sandy loam. Overall, the environmental conditions of Kuala Cangkoi and Ujong Pancu waters are still within the tolerance limits of Polinices to support their lives.